Performance Comparison Breadth First Search and Depth Limited Search on Eight Box - Ekawijana, Ardhian (International Journal of Psychosocial Rehabilitation, 2020)
Comparison of the performance of Breath First Search and Depth Limited Search views of the four parameters. DLS seen from memory usage, iterations, and time is superior because the solution is found to the left of the path. First Breath Searh is ahead in the optimal path to the discovery of the solution compared to DLS due to searching the horizontal way.